Granular Cell Odontogenic Tumor, an Extremely Rare Case Report - Atarbashi-Moghadam, Saede (J Dent (Shiraz), 2019)
The granular cell odontogenic tumor is an extremely rare odontogenic neoplasm which about 38 cases has been reported with sufficient documentation in the literature. It has a prominent predilection to occur in the posterior of mandible of middle-aged women. Here, we report a case of mandibular granular cell odontogenic tumor in a 57-year-old female with chief complaint of swelling and tooth mobility. As rarity of these lesions, their clinical behavior and prognosis are not clear; hence, reporting more such cases may be beneficial to correct diagnosis and prevent unnecessary treatment.